-137 (G/C) IL-18 promoter polymorphism in patients with inflammatory bowel disease - Haas, Stephan; Andreas Koch, W; Schreiber, Stefan; Reinhard, Iris; Koyama, Noriko; Singer, Manfred V.; Böcker, Ulrich (Scandinavian journal of gastroenterology, 2005)
Objective. There is strong evidence that genetic factors contribute to the susceptibility for inflammatory bowel diseases (IBD). Recently, IL-18 promoter polymorphisms were characterized as risk factors for inflammatory diseases such as sepsis, asthma and adult-onset Still's disease. The aim of this study was to determine whether the −137 (G/C) IL-18 promoter polymorphism was associated with IBD susceptibility. Material and methods. For association analysis, 470 patients with Crohn's disease (CD), 235 unrelated patients with ulcerative colitis (UC) and 347 controls were enrolled. Furthermore, 233 UC and 470 CD trios were included for segregation analysis. Genotyping was performed by application of the TaqMan MGB biallelic discrimination system. Results. When comparing genotype frequencies of CD and UC patients versus controls, no significant difference was found (p=0.089 and p=0.078, respectively). However, the Cochran-Armitage trend test revealed a rising probability for CD and UC with increasing number of G alleles (p=0.030 and 0.028, respectively) for the case-control analysis. On the contrary, the family-based transmission disequilibrium test (TDT) did not show an association of the G allele with CD or UC in 470 CD and 233 UC trios (p=0.53 and p=0.79, respectively). Conclusion. The −137 (G/C) IL-18 promoter polymorphism is not a susceptibility factor for IBD in a German cohort.